'Creating the community I want to be part of': Affinity-based organising in a small, progressive rustbelt city. (May 2021) - Currans, Elizabeth
This article explores a small city's response to the inauguration of Donald Trump in January 2017. Love, Resilience, Action Ypsilanti (LRAY) focused on community-building and the social justice history of Ypsilanti, Michigan to create a queer-affirming feminist event that intentionally referenced and diverged from national Women's Marches. In exploring intersectional social justice organising by a queer-dominated feminist group, I argue that organisers' emphasis on communal care in combination with direct action reflected an affinity-based understanding of community characteristic of this particular small progressive rustbelt city. This example demonstrates the importance of including small cities in urban LGBTQ research.